Time Trends and Monthly Variation in Swedish Acute Stroke Care - Darehed, David; Blom, Mathias; Glader, Eva-Lotta; Niklasson, Johan; Norrving, Bo; Eriksson, Marie (Frontiers in Neurology, 2019)
Background and Purpose: Studies of monthly variation in acute stroke care have led to conflicting results. Our objective was to study monthly variation and longitudinal trends in quality of care and patient survival following acute stroke. Methods: Our nationwide study included all adult patients (≥18 years) with acute stroke, (ischemic or hemorrhagic) admitted to Swedish hospitals from 2011 to 2016, and that were registered in The Swedish Stroke Register (Riksstroke). We studied how month of admission and longitudinal trends affected acute stroke care and survival. We also studied resilience to this variation among hospitals with different levels of specialization. Results: We included 132,744 stroke admissions. The 90-day survival was highest in May and lowest in January (84.1% vs 81.5%). Thrombolysis rates and door-to-needle time within 30 minutes increased from 2011 to 2016 (respectively 7.3% vs 12.8% and 7.7% vs 28.7%). Admission to a stroke unit as first destination of hospital care was lowest in January and highest in June (78.3% vs 80.5%). Stroke unit admission rates decreased in university hospitals from 2011 to 2016 (83.4% vs 73.9%), while no such trend were observed in less specialized hospitals. All the differences above remained significant (p<0.05) after adjustment for possible confounding factors. Conclusion: We found that month of admission and longitudinal trends both affect quality of care and survival of stroke patients in Sweden, and that the effects differ between hospital types. The observed variation suggests an opportunity to improve stroke care in Sweden. Future studies ought to focus on identifying the specific factors driving this variation, for subsequent targeting by quality improvement efforts.